Thermal conductivity and superconductivity in EuBa2Cu3O7-x - Izbizky, M.A.; Núñez Regueiro, M.; Esquinazi, P.; Fainstein, C. (American Physical Society, 1988)
Fil: Izbizky, M.A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina